Methods for determining hip and lumbosacral joint centers in a seated position from external anatomical landmarks. Issue 2 (21st January 2015) - Peng, Junfeng; Panda, Jules; Van Sint Jan, Serge; Wang, Xuguang
Abstract A global coordinate system (GCS) method is proposed to estimate hip and lumbosacral joint centers (HJC and LSJC) from at least three distances between joint center of interest and target anatomic landmarks (ALs). The distances from HJC and LSJC to relevant pelvis and femur ALs were analyzed with respect to usual pelvis and femur scaling dimensions. Forty six pelves and related pairs of femurs from a same sample of adult specimens were examined. The corresponding regression equations were obtained. These equations can be used to estimate HJC and LSJC in conditions where a very limited number of ALs are available: for example, during seated posture analysis as performed in the automotive industry. Compared to currently existing HJC and LSJC methods from ALs, the proposed method showed better results with an average error less than 11 mm.